Epidemiology of Respiratory Syncytial Virus-Associated Acute Lower Respiratory Tract Infection among Hospitalized Under-5s in Northwestern Nigeria - Garba, Maria Ahuoiza; Giwa, Fatima Jummai; Adelaiye, Hamdala; Olorukooba, Abiola Aira; Abdullahi, Fatima; Makarfi, Hauwa; Löwensteyn, Yvette; Bont, Louis; Abdurraheem, Fadlullah; Uudu, Ehi; Mudasir, Halima; Mazur, Natalie I (Journal of Pediatric Infectious Diseases, 2023)
Objective Globally, 33 million cases of respiratory syncytial virus (RSV) infections occur annually among under-fives (5s). Ninety-nine percent of deaths from RSV occur in low- and middle-income countries. Under-five pneumonia mortality in Nigeria was estimated at 140,520 in 2017, but RSV epidemiological data are scant due to poor awareness and limited testing. Vaccines for RSV are currently under development and RSV mortality data from this high mortality, low resource setting are essential to maximizing the potential benefit of vaccination as well as promoting vaccine uptake. This study aimed to describe the epidemiology of RSV-associated acute lower respiratory tract infection (ALRTI) in children younger than 5 years in Zaria, Northwestern Nigeria.Methods A prospective cohort study was conducted among children aged 1 month to 5 years who were hospitalized with ALRTI in the Emergency Pediatric Unit of a tertiary hospital in Zaria from November 2018 to October 2019. Naso-pharyngeal swabs were obtained for RSV testing using a point-of-care immunoassay technique.Results Thirty-three percent (35/106) of the children had RSV-related ALRTI. The median age of RSV-positive cases was 8 months (IQR 3–14). Two-thirds of children (68.6%, 24/35) were below 12 months. The RSV mortality rate was 5.7% (2/35). RSV occurred in 10 months of the year with peaks in March and July.Conclusion A third of admitted children with ALRTI were positive for RSV. Therefore RSV significantly contributes to childhood pneumonia and the dual seasonal peak observed in our study may have implications for vaccine implementation.
Keywords: respiratory syncytial virus; prevalence; epidemiology; seasonality; under-5s